Cassava based intercropping: a review - Mutsaers, H.J.W.; Ezumah, H.; Osiru, D. (Elsevier, 1993)
This paper reviews intercropping research for a particular case: cassava-based crop combinations. Cassava is dominated in combination with maize while it is the dominating species in combination with low-growing species. Combinations with maize or legumes show a real biological advantage over the sole crops reflected in (modified) Area × Time Equivalency ratio (ATER) values above unity. This is not the case with sweet potatoes. Success of maize+cassava mixtures depends on time and rate of recovery of cassava after maize harvest. Biological advantage tends to disappear when maize yield exceeds about 3.5 t ha−1. Under growing conditions or practices which result in high maize yield, intercropping cassava with maize is not biologically advantageous Biological advantage of intercropping with legumes decreases with the legumes' growth duration, which should not exceed 90 days. Physiological traits of cassava for successful intercropping with maize or with legumes are probably not the same, but their nature is not clear. Moderate early vigour and a high partitioning of dry matter to the storage roots after harvest of the associated crops seem important in both cases. Cassava breeding for sole cropping has resulted in varieties with good performance in intercropping. Whether varieties can be selected with better adaptation to intercropping cannot be concluded from the literature. Dry-matter distribution, in particular after harvest of the associated crop, seems important but more growth analytical studies are required. Usefulness of currently available crop models in the study of intercropping is doubtful.